2018
DOI: 10.1002/lt.25001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of abdominal shape on living liver donor outcomes in mini‐incision right hepatic lobectomy: Comparison among 3 techniques

Abstract: Although minimally invasive techniques for living donor hepatectomy have been developed, the surgical feasibility and limitations remain to be elucidated. The risks and outcomes involved need to be better understood prior to their widespread application. The aim of this study was to assess feasibility of minimally invasive donor hepatectomy by reviewing our experience. A total of 99 living donor liver transplantations performed between 2000 and 2016 were retrospectively reviewed. All 99 living liver donors und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…evaluated the impact of body habitus on perioperative donor outcomes in procedures using one of three different incisions (standard technique, hybrid technique, and mini‐laparotomy without laparoscopic assistance) and found that donors with a high BMI (>30), a large umbilical circumference (>90 cm), and a high celiac axis depth ratio (>0.41) had a longer operation time and hospital stay. These larger body habitus parameters were risk factors for higher postoperative complications in the mini‐laparotomy group .…”
Section: Laparoscopy‐assisted Donor Hepatectomymentioning
confidence: 90%
See 1 more Smart Citation
“…evaluated the impact of body habitus on perioperative donor outcomes in procedures using one of three different incisions (standard technique, hybrid technique, and mini‐laparotomy without laparoscopic assistance) and found that donors with a high BMI (>30), a large umbilical circumference (>90 cm), and a high celiac axis depth ratio (>0.41) had a longer operation time and hospital stay. These larger body habitus parameters were risk factors for higher postoperative complications in the mini‐laparotomy group .…”
Section: Laparoscopy‐assisted Donor Hepatectomymentioning
confidence: 90%
“…Although the most challenging aspects of donor right hepatectomy can be performed through a midline incision in LADH, managing unexpected intraoperative events remains a major concern, especially in cases of vascular injury in the deep area . Indeed, surgical exposure in LADH depends largely on the thickness of the donor's abdominal wall and visceral fat.…”
Section: Laparoscopy‐assisted Donor Hepatectomymentioning
confidence: 99%
“…Moreover, there are other factors that affect operative time other than the liver size. Anatomical variation in portal vein, hepatic vein, or bile duct may also prolong operative time [34,35] Abdominal muscularity or abdominal shape can also affect operative time [36]. Abdominal muscularity in donors with a low BMI could make abdominal inflation difficult, thereby providing a small working space.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the muscle layer is not interrupted, and, as a result, patients feel less abdominal wall pain than with the open hepatectomy [69] . However, the small incision of these techniques has drawbacks for obese patients with deep body cavities, such as longer operative duration, postoperative complications, and longer hospital stay, as it is difficult for surgeons to manage vascular injuries in these deeper areas [68,70,71] . Recent meta-analyses associated laparoscopic-assisted hepatectomy with fewer complications, less blood loss and pain, no mortality, faster recovery, better cosmetic result, and longer operation time [70,72] .…”
Section: Hand-assisted and Hybrid Donor Hepatectomymentioning
confidence: 99%
“…However, the small incision of these techniques has drawbacks for obese patients with deep body cavities, such as longer operative duration, postoperative complications, and longer hospital stay, as it is difficult for surgeons to manage vascular injuries in these deeper areas [68,70,71] . Recent meta-analyses associated laparoscopic-assisted hepatectomy with fewer complications, less blood loss and pain, no mortality, faster recovery, better cosmetic result, and longer operation time [70,72] . In other words, laparoscopic-assisted hepatectomy is a safe and feasible alternative to open hepatectomy for well-selected donors when performed by experienced teams [73] and can be gradually adopted by less-experienced groups [74,75] .…”
Section: Hand-assisted and Hybrid Donor Hepatectomymentioning
confidence: 99%